Mercury Pollution In Snow Cover Around Thermal Power Plants In Cities (Omsk, Kemerovo, Tomsk Regions, Russia) - Anna V. Talovskaya; Egor G. Yazikov; Nina A. Osipova; Elena E. Lyapina; Victoria V. Litay; George Metreveli; Junbeum Kim (GEOGRAPHY, ENVIRONMENT, SUSTAINABILITY, 2019)
Although snow cover is studied as an efficient scavenger for atmospheric mercury (Hg), up to now little is known about Hg behaviour in urban snow cover impacted by thermal power plants (TPPs) during the winter heating season. This study is focused on quantification of Hg in the particulate phase in snow cover and estimation of atmospheric particulate Hg (HgP) depositional fluxes around urban TPPs in cities of Omsk, Kemerovo, Yurga, Tomsk (the south part of Western Siberia, Russia) to provide new insight into Hg occurrence in urban snow. The results demonstrate that the mean Hg content in the particulate phase of snow varied from 0.139 to 0.205mg kg-1, possibly depending on thermal power of TPPs and fuel type used. The estimated mean atmospheric HgP depositional fluxes ranged from 6.6 to 73.1 mg km-2 d-1. Around thermal power plants atmospheric HgP depositional flux was controlled by particulate load. Higher Hg contents in the particulate phase of snow and higher atmospheric HgP depositional fluxes observed in relation to the background values, as well as high enrichment factors determined for Hg in the particulate phase of snow relative to the mean Hg content in the Earth’s crust showed that the snow pollution with Hg is of anthropogenic origin. The coexistence of Hg and S observed for the particulate phase of snow indicated the possible presence of mercury sulfide in this phase. The parameters like Hg content in the particulate phase of snow and HgP atmospheric flux can be used as markers for the identification of coal combustion emission sources.